Rainfall-runoff characteristics in a tropical forested catchment, Puchong, Selangor, Malaysia - Saito, Mariko; Tsujimura, Maki; Abu Bakar, Siti Nurhidayu (Japan Society of Hydrology and Water Resources, 2023)
This study aims to clarify the contributions of pre-event water to storm runoff using environmental tracers (dis‐ solved inorganic ions and stable isotopes) in a tropical forested catchment in Puchong, Selangor, Malaysia. We performed intensive sampling campaigns of stream water and throughfall for two storm events in July and November 2018. The discharge showed a low peak of 0.13 mm/h in event 1, with 18 mm of total rainfall, whereas event 2, with 50 mm of total rainfall, showed a quick discharge peak of 1.17 mm/h and a slow recovery of 0.39 mm/h. The nitrate concentration in the stream water during event 2 was higher than that in event 1. The temporal variations in nitrate ions indicate that subsurface water provided a dominant storm‐ flow in event 2. Hydrograph separations using silicate as a tracer revealed that pre-event water was the dominant com‐ ponent of the storm hydrograph (58–98%). Our results sug‐ gest that pre-event water plays an essential role in storm runoff of headwaters in humid tropical regions.